1994
DOI: 10.1093/geront/34.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Outcomes of Hospitalized Dementia Patients: From Home to Hospital to Discharge

Abstract: This study examined factors associated with willingness to continue in the caregiving role after the hospitalization of a relative with dementia. Interviews were conducted with 179 caregivers of hospitalized patients to determine the influences of predisposing, enabling, and need factors in the discharge decision. Logistic regression was used to identify variables predictive of caregivers taking patients home for those who were originally planning on doing so and for those who were originally undecided. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A family carer played a key role in the transition back home, and an early study by Cox and Verdieck 45 found that if there were formal services in place and the carer had assistance with medication, bathing and supervision, and support and counseling, then the patient tended to return home from hospital rather than making the transition to a care home. However, carers needed to know how to negotiate service provision and manage the care of the patient in conjunction with services, 25 particularly with regard to timing and levels of service provision that may fail to meet the families’ requirements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A family carer played a key role in the transition back home, and an early study by Cox and Verdieck 45 found that if there were formal services in place and the carer had assistance with medication, bathing and supervision, and support and counseling, then the patient tended to return home from hospital rather than making the transition to a care home. However, carers needed to know how to negotiate service provision and manage the care of the patient in conjunction with services, 25 particularly with regard to timing and levels of service provision that may fail to meet the families’ requirements.…”
Section: Resultsmentioning
confidence: 99%
“…37 The literature found that hospital discharge planning is very important to many carers 54 and that carers are seen as playing a key role in the patients’ discharge. 45 However, carers reported a lack of communication with health professionals, not being listened to and feeling undervalued as a resource. 53 A lack of communication and professional support may explain the reasons why some carers may not comply with hospital instructions, care plans, or appointments or refuse any help offered.…”
Section: Discussion Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that caregiver needs, as determined by stress and burden, are critical factors in the decision to use services. [13][14][15] …”
Section: Modelmentioning
confidence: 99%
“…Studies in stroke and dementia have shown that insurance type is a predictor of discharge disposition. 27,28 If insurance type predicts discharge disposi-tion, insurance status (whether or not the patient is insured) may also predict discharge disposition.…”
Section: Conceptual Modelmentioning
confidence: 99%